Sunnite Understanding of Fiqh Methodology - YÜKSEK, Ali; GÖKALP, Yusuf (Scientific Journal of Faculty of Theology, 2020)
In the life of the Prophet, there was no creed or political differentiation between Muslims, but after his death, some disagreements began to arise. Methodically different approaches began to emerge among Muslims to find solutions to the problems that arose due to these conflicts. Scholars, especially the prominent Companions, inevitably made ijtihad on religious matters. These different methodical approaches were effective in shaping belief, worship and social life. The emerging approaches were later named “Ahl al-Hadith” and “Ahl al-Ray” in the field of law, while in the field of faith they were called “Ahl al-Sunnah” and “Ahl al-Bidat”. In this study, In this study, we try to put forth the perception of the concept of Ahl al-Sunnah and the understanding of fiqh methodology of this school. We also mentioned the differences between Sunnite schools of fiqh methodology. In addition, in terms of subject integrity, we found it appropriate to give information about the basic topics of Sunnite books of fiqh methodology.